Overview of the Student Learning Environment of the Universitas Padjadjaran Nursing Profession Study Program - Aini, Erina Nur; Agustina, Hana Rizmadewi; Permana, Ryan Hara (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The learning environment is an important component in determining the quality and success of the nursing education curriculum. A learning environment that is not supportive can result in decreased student learning performance, including decreased interest and motivation, anxiety and stress, and reduced self-confidence. Evaluation of the learning environment helps improve the quality of the learning environment which consists of the learning process, teaching staff, academic achievement, learning atmosphere, and social environment. This research aims to identify a description of the learning environment for students in the Padjadjaran University nursing professional study program. This research design will use a quantitative descriptive research design. The sampling technique that will be used is proportionate stratified random sampling with 142 nursing professional students as samples. The instrument used is the Dundee Ready Education Environment Measure (DREEM) with 50 statement items. The data analysis that will be carried out is univariate analysis. The results of research on the learning environment dimension show an average score of 148.96/200 in the good category. The average is obtained for each sub-variable; learning process (35.44/48), teaching staff (33.74/44), academic achievement (25.44/32), learning atmosphere (34.49/48), and social environment (19.82/28). Academic achievement with the highest score and social environment with the lowest score. The assessment of the learning environment for nursing professional students shows the Good category, which means that the learning environment for the nursing profession is running well, although there are things that need to be improved and corrected to improve the quality of learning.